Evaluasi Penggunaan Lahan (Land Use) pada Kecamatan Longkib Kabupaten Subulussalam Tahun 2013 - Rizki Auliansyah Putra; Afifuddin Dalimunthe; Budi Utomo (Peronema Forestry Science Journal, 2015)
Land use and land cover is an important component in understanding the interaction of human activities with the ENVIronment. Forest management include the planning and supervision in Subulussalam city becomes very importnan to do in oreder to prevent degradation of the forest more severe. The porpose of this study was to quantify land use in 2013. This research methods to  ultilize remote sensing technology and geographical information system (GIS) an interpretation of Landsat-8 OLI/TIRS 2013. Classification results show that the District of Longkib It has 9 land cover classes. The results showed that the land cover is dominated Longkib District of open land.  Action needs structuring ecosystems and prevention in the use of land in the District Longkib.Keywords: land use, land cover, Landsat-8 OLI/TIRS 2013